Improving Teacher Competence in Blended Learning-Based Technology from a Gender Perspective - Halimatussakdiah, Halimatussakdiah; Azwar, Alfi Julizun; Sartika, Eka (Atthulab: Islamic Religion Teaching and Learning Journal, 2024)
This research discusses efforts to increase teacher competency in blended learning-based technology through a gender approach. Blended learning, which combines online and face-to-face learning methods, has the potential to increase interaction and learning accessibility, but requires adequate technological skills from teachers. By considering a gender perspective, this research explores the differences and gaps that may arise between male and female teachers in adopting blended learning technology. Data was collected through a survey of a number of teachers from various school levels who had access to blended learning training. The research results show that there are disparities in the use of technology, where gender, age and experience factors influence teacher competence in implementing learning technology. This research recommends gender-based training that supports all teachers in developing their technology skills, to create more inclusive and effective learning environments. Thus, increasing this competency not only supports teacher career development, but also improves student learning outcomes through the use of more adaptive and responsive technology. Penelitian ini membahas upaya peningkatan kompetensi guru dalam teknologi berbasis pembelajaran campuran (blended learning) melalui pendekatan gender. Blended learning yang menggabungkan metode pembelajaran daring dan tatap muka memiliki potensi untuk meningkatkan interaksi dan aksesibilitas pembelajaran, namun memerlukan keterampilan teknologi yang memadai dari guru. Dengan mempertimbangkan perspektif gender, penelitian ini mengeksplorasi perbedaan dan kesenjangan yang mungkin muncul antara guru pria dan wanita dalam mengadopsi teknologi blended learning. Data dikumpulkan melalui survei terhadap sejumlah guru dari berbagai tingkatan sekolah yang memiliki akses terhadap pelatihan blended learning. Hasil penelitian menunjukkan adanya disparitas dalam penggunaan teknologi, di mana faktor gender, usia, dan pengalaman mempengaruhi kompetensi guru dalam penerapan teknologi pembelajaran. Penelitian ini merekomendasikan pelatihan berbasis gender yang mendukung seluruh guru dalam mengembangkan keterampilan teknologi mereka, guna menciptakan lingkungan belajar yang lebih inklusif dan efektif. Dengan demikian, peningkatan kompetensi ini tidak hanya mendukung perkembangan karir guru, tetapi juga meningkatkan hasil belajar siswa melalui penggunaan teknologi yang lebih adaptif dan responsif.